Ecuador champion - Diario Vespertino La Prensa (Revista Universidad de Guayaquil, 1988)
The writing that we reproduce was published in 1938 by the Vespertino La Prensa newspaper, and reproduced in the April 1938 issue of the Municipal Magazine. It was one of the many articles published on the occasion of the fact that, in March 1938, in Lima, Peru, four Ecuadorian swimmers won the South American Swimming Championship. This important event was Ecuador’s first international sporting triumph. We make this new reproduction on the occasion of the fiftieth anniversary of the V South American Swimming Championships.